PENGUJIAN SIZE HYPOTHESIS DAN DEBT/EQUITY HYPOTHESIS YANG MEMPENGARUHI TINGKAT KONSERVATISMA LAPORAN KEUANGAN PERUSAHAAN DENGAN TEHNIK ANALISIS MULTINOMIAL LOGIT - LUCIANA SPIKA ALMILIA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2005)
This research has a purpose to provide empirical evident about political cost hypothesis and debt/equity hypothesis. Political cost hypotesis said that some firms that are more vulnerable to political cost than the others manage income downward to avoiding the attention of government and regulator. Debt/equity hypothesis said that the larger the debt/equity ratio, the more likely the firms is to increase current period reported earning or optimist financial statement. The conservatism proxy used in this research is first, accruals obtained form differences between net income and cash flow. Second, market to book value ratio. The statistic methode which is used to test on the research hypothesis is multinomial logit. The result of reseach shows that: first, the small firms are more politically sensitive than larger firms or financial statement more conservative. Second, the larger a firms debt/equity ratio, the more likely the firm's manager is to report financial statement more optimist.